Perioperative time-management methods to reduce waiting times for elective surgery: a systematic review. Issue 12 (2nd December 2022) - Rathnayake, Dimuthu; Clark, Mike; Jayasinghe, Viraj; Udayanga, Viraj; Qudairat, Eiad
Abstract : Perioperative processes and adherence to scheduled times are crucial for efficient performance in operating theatres. This systematic review investigated the effects of efficient perioperative systems on the timeliness of upstream and downstream processes in surgical care pathways, looking at how these methods could reduce overall patient waiting times for elective surgery. The authors searched PubMed, EMBASE, SCOPUS, Web of Science and Cochrane databases for articles published after 1 January 2014. Both randomised and non-randomised studies were considered. A total of 7543 publications were screened, of which 20 were eligible for analysis. The studies varied widely in design, scope, reported outcomes and overall quality. Analysis demonstrated that a substantial amount of time could be saved through efficient scheduling and planning of perioperative processes, which could reduce overall patient waiting time for elective surgeries. Further evaluation with higher quality study designs and rigour is recommended for firmer conclusions.